Negative Unintended Consequences of the GOAL Scholarship on Local Private Tertiary Institutions in Guyana - Paul (Sr.), Stanley A. V.; Paul (Jr.), Stanley A. V. (Integrated Journal for Research in Arts and Humanities, 2024)
The GOAL (Guyana Online Academy of Learning) Scholarship initiative aims to enhance educational accessibility by providing Guyanese students with free tuition at various foreign tertiary institutions. While the program is designed to democratize education and offer valuable opportunities, it has inadvertently created significant challenges for local private tertiary institutions. This article explores these unintended consequences, focusing on the financial and operational impacts on private institutions, and proposes strategies to balance the benefits of the scholarship with the sustainability of the local private education sector.